Proceedings of the 2003 ACM SIGMETRICS International Conference on Measurement and Modeling of Computer Systems 2003
DOI: 10.1145/781027.781039
|View full text |Cite
|
Sign up to set email alerts
|

Fluid models and solutions for large-scale IP networks

Abstract: In this paper we present a scalable model of a network of Active Queue Management (AQM) routers serving a large population of TCP flows. We present efficient solution techniques that allow one to obtain the transient behavior of the average queue lengths, packet loss probabilities, and average end-to-end latencies. We model different versions of TCP as well as different versions of RED, the most popular AQM scheme currently in use. Comparisons between our models and ns simulation show our models to be quite ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 15 publications
0
69
0
Order By: Relevance
“…The congestion window size of the cumulative flow is given in (18), and the number of flows in the slow start phase in a TD-period is Using expressions for from (14) and for from (23), we have (24) Finally, the steady-state throughput of parallel flows can be calculated as (25) where is given in (24) and is defined in (17).…”
Section: A Model With Timeoutsmentioning
confidence: 99%
See 1 more Smart Citation
“…The congestion window size of the cumulative flow is given in (18), and the number of flows in the slow start phase in a TD-period is Using expressions for from (14) and for from (23), we have (24) Finally, the steady-state throughput of parallel flows can be calculated as (25) where is given in (24) and is defined in (17).…”
Section: A Model With Timeoutsmentioning
confidence: 99%
“…There is now a wealth of TCP models available (e.g., [11]- [14]), many of which are better than the model in [1] in some aspect, but they are all much more complex, making their practical application much harder. Some effort was also made to model a number of TCP flows sharing a bottleneck instead of focusing on just a single one [14]- [21]. The usability of these works is limited because they assume that the flows under consideration are alone in the network.…”
Section: Related Workmentioning
confidence: 99%
“…There has been much research on the network simulation based on fluid models [3,4,9,8]. Liu et al [3] compare packet-level simulations and fluid models in terms of relative efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…A scalable model of a network of AQM routers is presented in [9], and the transient behavior of the average queue length, packet loss probabilities, and average end-to-end latencies have been observed. It is shown that their fluid model is accurate and requires substantially less time to solve, especially when workloads and bandwidths are high.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation